(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Village Funds are a means of increasing income sources in each village. The increase in village income provided by the government is used to improve community service facilities in the form of fulfilling basic needs, strengthening village institutions and other activities needed by the village community, which are decided through the Village Musrenbang. This problem is related to the condition of village officials whose human resources are suspected to be relatively low quality, as well as the community’s lack of critical thinking regarding the management of the village income and expenditure budget (APBDesa). The purpose of the Community Partnership Program is to provide counseling and assistance to the Poopoh Village community so that they can participate in monitoring and overseeing the effective and efficient management of Village Funds so that their benefits can be enjoyed by the village community. The results of this Community Service can be concluded that the Poopoh village officials are already capable of managing village funds administratively and in applications and also have a strong motivation to improve their ability to manage village funds better in the future so that village fund management can be utilized and accounted for properly.